2007
DOI: 10.1589/jpts.19.235
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Health Promotion Program Consisting of Easy and Simple Exercises for Community Living Elderly People

Abstract: Abstract. The purpose of this study was to test the efficacy of a health promotion program consisting of simple exercises among healthy elderly people in a community. The participants were healthy and elderly people, who were picked out from the users of a sports recreation facility. We carried out physical fitness measurements and instructed on exercises to participants. The evaluations were grip strength, knee extensor strength, sitting trunk flexion, falling-stick reaction time, one leg stance, Functional R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…The results were also similar to the findings of the study by Yu et al 13 ) , in which resistance exercises were performed using an elastic band for 12 weeks, three times each week, leading to improvements in muscular endurance (sitting and standing up from a chair) and balance (functional reach). However, the results were contrary to those of the study by Kazumasa et al 14 ) , in which an easy and simple resistance exercise program was implemented for the elderly of a local community. The eight-week exercise program conducted in the present study was found to be effective at enhancing the physical functions of the elderly.…”
Section: Discussioncontrasting
confidence: 96%
“…The results were also similar to the findings of the study by Yu et al 13 ) , in which resistance exercises were performed using an elastic band for 12 weeks, three times each week, leading to improvements in muscular endurance (sitting and standing up from a chair) and balance (functional reach). However, the results were contrary to those of the study by Kazumasa et al 14 ) , in which an easy and simple resistance exercise program was implemented for the elderly of a local community. The eight-week exercise program conducted in the present study was found to be effective at enhancing the physical functions of the elderly.…”
Section: Discussioncontrasting
confidence: 96%
“…The mechanisms underlying these links are complex, because it should be considered that effect of exercise per se on improvements of the POMS in both groups. However, it was reported that a health promotion program consisting of easy and simple exercise improved psychological attitudes including a subscale of the POMS, indicating that consecutive exercise per se may be useful for improvement of psychological stress 27 ) . Thus, although future studies are warranted, our results may indicate that forest walking can improve the POMS, irrespective of MAP changes, suggesting that forest walking may be a potential strategy to reduce psychological stress in middle-aged and elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…Ideal healthcare professionals for future community-based medicine are also required to be committed to regional development measures. Particularly, in the field of musculoskeletal improvements, many physical therapists also play active roles in their communities, and there have been many reports about activities for long-term care in Japan 1,2) . We think that the ideal Japanese physical therapists of the future should be committed to a flexible approach to meet the demands of their communities.…”
Section: Introductionmentioning
confidence: 99%